The Role of Ignatian Spirituality as a Form of Contribution to Increase Youth Involvement in Service at St. Stanislaus Church, Girisonta Parish - Clara Shinta Wibowo; Nerita Setiyaningtiyas; FR. Wuriningsih (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
Girisonta Parish, with Saint Stanislaus as its patron and inspired by the spirit of Saint Ignatius, aims to cultivate the Ignatian spirit among its parishioners. However, this spirit has not been significantly evident, as reflected in the low involvement of young people in church services. This study explores the role of Ignatian Spirituality in enhancing the participation of Young Catholics (OMK) in services at Saint Stanislaus Church, Girisonta Parish. Ignatian Spirituality, rooted in the teachings and spiritual experiences of Saint Ignatius Loyola, has the potential to strengthen the motivation, commitment, and quality of service among young people in the church environment. Using a qualitative research method with a case study approach, data was gathered through in-depth interviews, participatory observations, and document analysis of parish records. The findings indicate that the application of Ignatian Spirituality elements, such as contemplation, reflection, and action, along with other values, positively impacts the spiritual awareness, sense of belonging, and service-oriented mindset of OMK. This study also identifies the challenges in integrating Ignatian Spirituality into youth pastoral efforts and provides practical recommendations for developing youth programs based on Ignatian Spirituality. The contribution of this study lies in offering both a theoretical and practical framework for strengthening Catholic youth ministry through a transformative and spiritually rich approach.